Kinetic and thermodynamic studies of bovine serum albumin interaction with ascorbyl palmitate and ascorbyl stearate food additives using surface plasmon resonance. (25th April 2018) - Fathi, Farzaneh; Mohammadzadeh-Aghdash, Hossein; Sohrabi, Yousef; Dehghan, Parvin; Ezzati Nazhad Dolatabadi, Jafar
Highlights: AP and AS interaction with BSA was investigated. Formation of the additive–BSA complex was approved by dose-response sensorgrams. Positive values of ΔH and ΔS showed that hydrophobic forces are acting forces. The binding between BSA and food additives was enthalpy-driven. Abstract: Ascorbyl palmitate (AP) and ascorbyl stearate (AS) are examples of food additives, which have extensive use in food industry. In this study, we evaluated the interaction of bovine serum albumin (BSA) with AP and AS using surface plasmon resonance (SPR). In order to immobilize BSA, carboxymethyl dextran hydrogel (CMD) Au chip was used. After activation of carboxylic groups, BSA was immobilized onto the CMD chip through covalent amide binding formation. AP and AS binding to immobilized BSA at different concentrations was assessed. The dose–response sensorgrams of BSA upon increasing concentration of AP and AS have been shown. The low value of equilibrium dissociation constant or affinity unit (KD ) showed high affinity of both AP and AS to BSA. The KD value for binding of AP and AS to BSA were 4.09 × 10 −5 and 1.89 × 10 −5, at 25 °C. Overall, the attained results showed that AP and AS molecules can bind to BSA.